Mapping of Minimal Motifs of B-Cell Epitopes on Human Zona Pellucida Glycoprotein-3 - Wan-Xiang Xu; Ya-Ping He; Jian Wang; Hai-Ping Tang; Hui-Juan Shi; Xiao-Xi Sun; Chao-Neng Ji; Shao-Hua Gu; Yi Xie (Clinical and Developmental Immunology)
The human zona pellucida glycoprotein-3 (hZP3) by virtue of its critical role during fertilization has been proposed as a promising candidate antigen to develop a contraceptive vaccine. In this direction, it is imperative to map minimal motifs of the B cell epitopes (BCEs) so as to avoid ZP-specific oophoritogenic T cell epitopes (TCEs) in the ZP3-based immunogens. In this study, based on known results of mapping marmoset and bonnet monkey ZP3 (mstZP3 and bmZP3), two predictable epitopes23–30  and  301–320 on hZP3 were first confirmed and five minimal motifs within four epitopes on hZP3 were defined using serum to recombinant hZP3a22–176 or hZP3b177–348 as well as a biosynthetic peptide strategy. These defined minimal motifs were QPLWLL23–28 for hZP323–30, MQVTDD103–108 for hZP393–110, EENW178–181 for hZP3172–190, as well as SNSWF306–310 and EGP313–315 for hZP3301–320, respectively. Furthermore, the antigenicity of two peptides for hZP3172–187 and hZP3301–315 and specificity of the antibody response to these peptides were also evaluated, which produced high-titer antibodies in immunized animals that were capable of reacting to ZP on human oocytes, r-hZP3b177–348 protein, as well as r-hZP3172–190, r-hZP3303–310, and r-hZP3313–320 epitope peptides fused with truncated GST188 protein.